Our polar flight : the Amundsen-Ellsworth polar flight - Amundsen, Roald , 1872-1928; Ellsworth, Lincoln , 1880-1951 (Dodd, Mead, 1925)
by Roald Amundsen and Lincoln Ellsworth and other members of the expedition. Illustrated from photographs taken on the expedition. --